Teams do inflict costly third-party punishment as individuals do: Experimental evidence - Kenju Kamei (Games, 2021)
Initiated by the seminal work of Fehr and Fischbacher (Evolution and Human Behavior (2004)), a large body of research has shown that people often take punitive actions towards norm violators even when they are not directly involved in transactions. This paper shows in an experimental setting that this behavioral finding extends to a situation where a pair of individuals jointly decides how strong a third-party punishment to impose. It also shows that this punishment behavior is robust to the size of social distance within pairs. These results lend useful insight since decisions in our everyday lives and also in courts are often made by teams.
Keywords: 330; dilemma; experiment; social norms; team decision making; third-party punishment